The incidence and management of cutaneous adverse events of the epidermal growth factor receptor inhibitors - Owczarek, Witold; Słowińska, Monika; Lesiak, Aleksandra; Ciążyńska, Magdalena; Maciąg, Aldona; Paluchowska, Elwira; Marek-Józefowicz, Luiza; Czajkowski, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Overexpression of the epidermal growth factor receptor (EGFR) is found in many cancers, including those of the head and neck area, non-small-cell lung cancer, and colorectal, cervical, prostate, breast, ovary, stomach, and pancreatic cancer. The EGFR inhibitors are used at present in the treatment of such cancers. Skin lesions that develop during and after cancer treatment may be due to specific cytostatics, molecular-targeted drugs, radiation therapy, complementary therapy, or the cancer itself, and hence knowledge is essential to distinguish between them. The mechanism through which skin toxicity arises during treatment with EGFR inhibitors is not well known, but seems to be due to the modification of the RAS/RAF/MEK/ERK signal path associated with its activation, which results in the similarity between the adverse effects of EGFR inhibitors and the treatment of melanoma with BRAF and MEK inhibitors. The most common side effects are pruritus, xerosis, papulopustular rash, hand-foot skin reaction, alopecia and dystrophy of the hair, and paronychia. This work presents options for prevention and suggestions for managing these adverse events, which are of importance in the care of patients undergoing oncological treatment.